USING Y CHART TECHNIQUE TO IMPROVE THE DESCRIPTIVE TEXT WRITING SKILL OF THE SEVENTH GRADERS OF SMP 2 BOROBUDUR - Adirga Lucky Purnama (Faculty of Education and Teachers Training, 2018)
Writing is one of the language skills which has an important role for the students to express their feeling and ideas. However, the seventh graders of SMP Negeri 2 Borobudur in the school year 2017/2018 still got difficulty in writing, especially in writing descriptive text. There are two objectives of this research. First, it is to know how great the use of Y Chart Technique can increase the learning motivation of descriptive text writing of the seventh graders of SMP N 2. Second, it is to know how great the improvement of the descriptive text writing skill of the seventh graders of SMP N 2 Borobudur in the school year 2017/2018 who are taught by using Y Chart Technique. The writer conducted a classroom action research. The subject of this research was the class of VII A of SMP Negeri 2 Borobudur in the school year 2017/2018 involving 17 females and 6 males. The writer implemented three phases in this research; they are Pre-Cycle, Cycle I and Cycle II. The writer used observation sheet, questionnaire, and documentations to collect the data. Based on the above results, the writer concludes that the use of Y Chart Technique can increase the students’ learning motivation in writing descriptive text and there is a great improvement of the descriptive text writing skill of the tenth graders of SMP Negeri 2 Borobudur in the school year 2017/2018. The writer suggests the teachers and the students to use Y Chart technique as an alternative teaching and learning.